Authoritarian Model Can Greatly Affect Children’s Temper Tantrums during The Covid 19 Pandemic. - Mutmainnah, Mutmainnah; Kusuma, Tesya Cahyani; Mahyuiddin, Muhammad Junaedi (Universitas Muhammadiyah Enrekang, 2023)
The study aims to determine whether the authoritarian parenting pattern of parents during the COVID-19 pandemic affects the tendency of early childhood temper tantrums in Tangru, Enrekang regency, in South Sulawesi. This research employs quantitative data, which is an investigation that goals to explain existing phenomena by using statistics to obtain an overview and characteristics of the situation being analyzed. The population includes all parents in Tangru who have early childhood, namely 125 families with a sample of 30 people. Purposive random sampling was used to collect samples, with the criteria of respondents having children who have temper tantrums. With traits such as loud crying, whining, hitting, biting, scratching, cursing, fussing, and rolling on the floor. Techniques for collecting information involve observation, questionnaires, and documentation. 1) The authoritarian parenting pattern of parents during the COVID-19 pandemic was included in the high category with the highest frequency results, namely 18 respondents with a percentage of 60%. The above authoritarian parenting reflects the parents' outlook, which is characterized by strict rules and limiting children's freedom, 2) Temper tantrums in early childhood are included in the very high category due to the child's desire to get something unfulfilled; 3) The hypothesis in this study is accepted. This appears to mean that there is an influence between the authoritarian parenting pattern of parents during the COVID-19 pandemic and the tendency to temper tantrums in early childhood in Tangru Village, where the authoritarian parenting style of family members is getting higher the child has more tantrums.